SYNTHESIS AND CHARACTERIZATION OF ZNO-CARBON NANOPOROUS COMPOSITE BASED ON ZIF-8 AS LITHIUM-ION BATTERY ANODE - Febrian, Rizki
Lithium-ion batteries are currently becoming very popular because of the increasing of renewable energy and electric vehicles application. The application depend on the performance of the lithium-ion battery. One of the components of the lithium-ion battery is anode. Compositing between metal oxide and carbon is strategy to improve the performance of lithium-ion battery anode, such as the ZnO-Carbon nanoporous composite synthesized in this study. Based on the results of previous studies, the composite between metal oxide and carbon produces a material with high conductivity, capacity, and stability. This is due to the high theoretical capacity of metal oxides, on the other hand carbon acts as a lithium ion accelerator and supports the structural stability of metal oxides. One of the precursors or templates used to produce metal oxide and carbon composites is Metal Organic Frameworks (MOFs), such as ZIF-8 for ZnO-Carbon nanoporous. These metal organic frameworks is used for various applications, one of which is energy storage devices such as lithium-ion battery anodes. The advantages of the ZnO-Carbon nanoporous composite anode based on ZIF-8 are its large surface area and porosity. This surface area and porosity can be controlled so that it is appropriate for the ion intercalation process in lithium-ion batteries. In this study ZIF-8 was synthesized using metallic zinc nitrate hexahydrate and organic ligand imidazole. The solvents used were methanol and dimethylformamide. The method used is non-solvothermal through precipitation at room temperature for 1 day. After obtaining ZIF-8 powder, it was then carbonized at temperatures of 500, 600, 700°C in a nitrogen gas environment so that 3 samples were obtained, namely ZnO-C 500, ZnO-C 600, and ZnO-C 700. The type of characterization used was XRD, SEM/EDS, TEM, BET, FTIR, and TGA. The results show that in ZnO-C 500, there is still a mixture of organic material from ZIF-8, in ZnO-C 600 and ZnO-C 700 there is already pure ZnO. The type of ZnO crystal formed is a hexagonal type of Wuritze which has the same parameters with the database. In the three samples, beside ZnO-C, there was also nitrogen doping. The intermediate morphology was found in ZnO-C 500 and ZnO-C 600, while the morphology of the nanospheres was found in ZnO-C 700. Based on the definition of nanomaterials, the three samples produced is nanomaterials, where the smallest morphological diameter was in ZnO-C 700, which was 33.44 -52.92 nm. The three samples also have a porous character with a nano-sized pore radius. The largest surface area and pore volume are in ZnO-C 700, 517.67 m2/g and 1.73 cm3/g. Cyclic Voltammetry (CV) testing was carried out using a 3-electrode system. Active material as working electrode, lithium foil as reference and counter electrode. The active material was made by adding a binder carboxymethyl cellulose and a conductive agent super-p carbon to the ZnO-C composite synthesized with N-methyl-2-pyrrolidone as solvent. The CV test results showed the formation of 3 reduction peaks. The first peak occurs in a reduction reaction in the conversion process, the second peak occurs in a reduction reaction in the alloying process, and the third peak occurs in a solid electrolyte interface (SEI) reaction. The highest diffusion coefficient is in ZnO-C 700 with a value of 3.67 x 10-8 cm2/s. This means that ZnO-C nanoporous is a high performance material for anodes. ZnO-C 700 also has the highest capacitive property, which is 2,530 Farads. The capacitive properties of the three samples indicate that these capacitive properties are influenced by the morphology, porosity, and surface area of the material.